Influence of cadmium and mercury on activities of ligninolytic enzymes and degradation of polycyclic aromatic hydrocarbons by Pleurotus ostreatus in soil - Baldrian, P; in Der Wiesche, C; Gabriel, J; Nerud, F; Zadrazil, F (Applied and environmental microbiology, 2000)
The white-rot fungus Pleurotus ostreatus was able to degrade the polycyclic aromatic hydrocarbons (PAHs) benzo[a]anthracene, chrysene, benzo[b]fluoranthene, benzo[k]fluoranthene, benzo[a]pyrene, dibenzo[a,h]anthracene, and benzo[ghi]perylene in nonsterile soil both in the presence and in the absence of cadmium and mercury. During 15 weeks of incubation, recovery of individual compounds was 16 to 69% in soil without additional metal. While soil microflora contributed mostly to degradation of pyrene (82%) and benzo[a]anthracene (41%), the fungus enhanced the disappearance of less-soluble polycyclic aromatic compounds containing five or six aromatic rings. Although the heavy metals in the soil affected the activity of ligninolytic enzymes produced by the fungus (laccase and Mn-dependent peroxidase), no decrease in PAH degradation was found in soil containing Cd or Hg at 10 to 100 ppm. In the presence of cadmium at 500 ppm in soil, degradation of PAHs by soil microflora was not affected whereas the contribution of fungus was negligible, probably due to the absence of Mn-dependent peroxidase activity. In the presence of Hg at 50 to 100 ppm or Cd at 100 to 500 ppm, the extent of soil colonization by the fungus was limited.
Keywords: Biodegradation, Environmental; biodegradace; Culture Media; Cadmium; Lignin; Mercury; Soil Microbiology; kadmium; Soil Pollutants; látky znečišťující půdu; lignin; půdní mikrobiologie; polycyklické aromatické uhlovodíky; rtuť; Polycyclic Aromatic Hydrocarbons; Pleurotus; kultivační média